Local Chemical Stimulation of Neurons with the Fluidic Force Microscope (FluidFM). Issue 10 (2nd November 2017) - Aebersold, Mathias J.; Dermutz, Harald; Demkó, László; Cogollo, José F. Saenz; Lin, Shiang‐Chi; Burchert, Conrad; Schneider, Moritz; Ling, Doris; Forró, Csaba; Han, Hana; Zambelli, Tomaso; Vörös, János
Abstract: Physiological communication between neurons is dependent on the exchange of neurotransmitters at the synapses. Although this chemical signal transmission targets specific receptors and allows for subtle adaptation of the action potential, in vitro neuroscience typically relies on electrical currents and potentials to stimulate neurons. The electric stimulus is unspecific and the confinement of the stimuli within the media is technically difficult to control and introduces large artifacts in electric recordings of the activity. Here, we present a local chemical stimulation platform that resembles in vivo physiological conditions and can be used to target specific receptors of synapses. Neurotransmitters were dispensed using the force‐controlled fluidic force microscope (FluidFM) nanopipette, which provides exact positioning and precise liquid delivery. We show that controlled release of the excitatory neurotransmitter glutamate induces spiking activity in primary rat hippocampal neurons, as measured by concurrent electrical and optical recordings using a microelectrode array and a calcium‐sensitive dye, respectively. Furthermore, we characterized the glutamate dose response of neurons by applying stimulation pulses of glutamate with concentrations from 0 to 0.5 mm . This new stimulation approach, which combines FluidFM for gentle and precise positioning with a microelectrode array read‐out, makes it possible to modulate the activity of individual neurons chemically and simultaneously record their induced activity across the entire neuronal network. The presented platform not only offers a more physiological alternative compared with electrical stimulation, but also provides the possibility to study the effects of the local application of neuromodulators and other drugs. Abstract : Stimulate your neurons chemically : Networks of neurons cultured in vitro are a crucial tool for neuroscience. The authors chemically stimulate neurons locally by combining the force‐controlled nanopipette FluidFM with an electrical microelectrode array and optical activity recordings. Using this platform, they characterize the glutamate dose response of neurons by applying stimulation pulses of glutamate with concentrations from 0 to 0.5 mm .